Percepção de auditores internos acerca da aplicabilidade do coso 2013 como instrumento de avaliação dos controles internos - Rodrigues, Alexandre (2016)
The main purpose of this research consists in verifying the applicability of COSO 2013 as an evaluation instrument of internal controls. The main justifications for this study are: (1) the new version of the internal controls framework (COSO 2013) has recently substituted, in December/2014, the version that was in force since 1992; the performance of the internal auditor is directly associated to the evaluation of internal controls; (3) previous studies were not identified to confirm, or not, the applicability of a methodology without exclusive regulatory bias of SOX. Classified as descriptive, the research covered internal auditors and audit managers. The questionnaire was chosen as the instrument to collect data, being the pretest conducted with participation of internal audit professionals with different functions and background. The sample, obtained by accessibility criteria, was formed by 155 (a hundred and fifty-five) professionals. We applied the following nonparametric tests: Mann-Whitney, Kruskal-Wallis, Qui-Square and Spearman coefficient. In line with the existent literature, which relates the COSO and the internal audit as ways of reducing the agency conflict, the analysis of the data showed that the professionals, besides considering it useful, recognize the applicability of COSO 2013 as an evaluation instrument of internal controls, being highlighted the importance of the emanating principles, with emphasis to the principle number one (integrity and ethical values). In relation to the use, COSO 2013, with a higher incidence, and COSO 2012, in sequence, are the most applied frameworks, while Turnbull and CoCo, frameworks in literature, were not even mentioned. In relation to the principles, number ten, internal controls , is the most used in the evaluations, and principle four, related to the competence of the key-area professionals, in contrast, is the less used. COSO 2013 also proved to be a strong inductor of audit attributes in literature, highlighting quality and objectivity. When it comes to the reasons suggested to adoption, we highlight the relevance that the subjects inserted in the methodology represent to the audit and, about the reasons that might stop the using, we highlight the lack of knowledge existent. The positive perception about the application, in general, is related to the organization and/or audit area being large, the organization being subject to some standard control and, last, to the fact that audit area is already using some framework. Professionals that use the methodology consider that the scope should be expanded, and the ones that do not use it consider that the methodology should be adopted. Last, despite the perceived applicability, we highlight, in general, that the utilization is strongly associated to the large audit areas, or whose respective organizations are subject to some standard control.